In defence of governance: Ethics review and social research - Sheehan, M; Dunn, M; Sahan, K (BMJ, 2017)
There is a growing body of literature that has sought to undermine systems of ethical regulation, and governance more generally, within the social sciences. In this paper, we argue that any general claim for a system of research ethics governance in social research depends on clarifying the nature of the stake that society has in research. We show that certain accounts of this stake-protecting researchers' freedoms; ensuring accountability for resources; safeguarding welfare; and supporting democracy-raise relevant ethical considerations that are reasonably contested. However, these accounts cannot underpin a general claim in favour of, or against, a system of research ethics governance. Instead, we defend governance in social research on the grounds that research, as an institutionalised form of enquiry, is a constitutive element of human flourishing, and that society ought to be concerned with the flourishing of its members. We conclude by considering the governance arrangements that follow from, and are justified by, our arguments.